2008
DOI: 10.1158/1535-7163.mct-07-0528
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant cathepsin S propeptide attenuates cell invasion by inhibition of cathepsin L–like proteases in tumor microenvironment

Abstract: Human cathepsin L along with cathepsin S, K, and V are collectively known as cathepsin L -like proteases due to their high homology. The overexpression and aberrant activity of each of these proteases has been implicated in tumorigenesis. These proteases contain propeptide domains that can potently inhibit both their cognate protease and other proteases within the cathepsin L -like subfamily. In this investigation, we have produced the cathepsin S propeptide recombinantly and have shown that it is a potent inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 48 publications
0
12
1
Order By: Relevance
“…Cathepsin L is a widely expressed cysteine protease with a major role in lysosomal proteolysis, protein processing, matrix degradation, and tissue remodeling, and it has been linked to the invasive phenotype in many cancers (24,25). Inhibition of cathepsin L activity by synthetic inhibitors and by the cathepsin S propeptide can reduce invasiveness of a number of human cancer cell lines (42), and prevention of cathepsin L secretion by introducing an overexpressed intracellular anticathepsin single chain variable antibody fragment dramatically reduced melanoma cell metastasis (43). We propose that SCCA-1 and heparin may combine to facilitate an endogenous mechanism for regulation of extracellular cathepsin activity and cathepsin-mediated metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Cathepsin L is a widely expressed cysteine protease with a major role in lysosomal proteolysis, protein processing, matrix degradation, and tissue remodeling, and it has been linked to the invasive phenotype in many cancers (24,25). Inhibition of cathepsin L activity by synthetic inhibitors and by the cathepsin S propeptide can reduce invasiveness of a number of human cancer cell lines (42), and prevention of cathepsin L secretion by introducing an overexpressed intracellular anticathepsin single chain variable antibody fragment dramatically reduced melanoma cell metastasis (43). We propose that SCCA-1 and heparin may combine to facilitate an endogenous mechanism for regulation of extracellular cathepsin activity and cathepsin-mediated metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work indicates that CTSS may also play a role in the diminution of the lung's antimicrobial defenses thereby favoring conditions for bacterial infection (13,14,23). Furthermore, given its potent elastinolytic activity (17)(18)(19)(20)53), it is possible that CTSS may play a role in tissue damage and remodeling present in early CF (2, 3, 6, 7), an increasingly recognized clinical finding over the last 5 years. In addition, the presence of elevated CTSS in the CF airways may explain, in part, why previous therapeutic approaches to protease neutralization in the CF lung, which have not taken elevated CTSS activity into account, have not been entirely successful to date.…”
Section: Original Articlementioning
confidence: 99%
“…In spite of this, it has been reported that CatS is overexpressed in many cancer cells and tissues, 22,23 and recently developed radiation treatment technology is able to focus the radiation dose on the area affected by the cancer so that it does not impact unaffected cells. 24 Therefore, given the recent interest in the role that CatS regulation plays in several physiological and pathological processes, radiation-induced CatS expression may give rise to novel therapeutic strategies. 6 -A model illustrating the role of CatS in radiation response.…”
Section: Discussionmentioning
confidence: 99%